If you build it, will they come? Is test site availability a root cause of geographic disparities in COVID-19 testing?. (March 2023) - Hendricks, B.; Price, B.S.; Dotson, T.; Kimble, W.; Davis, S.; Khodaverdi, M.; Halasz, A.; Smith, G.S.; Hodder, S.
Abstract: Objectives: The purpose of this study was to examine the relationship between test site availability and testing rate within the context of social determinants of health. Study design: A retrospective ecological investigation was conducted using statewide COVID-19 testing data between March 2020 and December 2021. Methods: Ordinary least squares and geographically weighted regression were used to estimate state and ZIP code level associations between testing rate and testing sites per capita, adjusting for neighbourhood-level confounders. Results: The findings indicate that site availability is positively associated with the ZIP code level testing rate and that this association is amplified in communities of greater economic deprivation. In addition, economic deprivation is a key factor for consideration when examining ethnic differences in testing in medically underserved states. Conclusion: The study findings could be used to guide the delivery of testing facilities in resource-constrained states.